Marquage héraldique, cartographie et histoire des lignages : les relevés de Gaignières à la chapelle des chanoinesses de Luynes - Sarah Héquette (Les Cahiers de l'École du Louvre)
In 1699 François-Roger de Gaignières and Louis Boudan visited the canonesses’ chapel in Luynes, Touraine, which had been commissioned by Hardouin IX de Maillé in the late fifteenth century. Judging by the drawings they made on the spot, Gaignières’ interest in the building lay in its profusion of symbols: six of Louis Boudan’s ten drawings focused on the heraldry of the families who had left their mark on the place. In all, twelve shields, made up of fifteen different quarters, were copied by Gaignières and bear witness to the filiation, alliances and genealogy of the Maillé family. This article will examine the chapel’s heraldic programme, identifying the figures represented and studying the way in which their coats of arms occupy the space. Secondly, it will explore how digital humanities, and geodata in particular, allow us to gain a better understanding of the methods and logic underlying this emblematic marking. Gaignières, through his drawings of the Luynes chapel, provides an account of the mapping of families and lineages over a territory that goes beyond the boundaries of Touraine.